A cleaner approach for high-efficiency regeneration of base and precious metals from waste printed circuit boards through stepwise oxido-acidic and thiocyanate leaching. (July 2022) - Rezaee, Mohammad; Abdollahi, Hadi; Saneie, Roozbeh; Mohammadzadeh, Amirhossein; Rezaei, Ali; Karimi Darvanjooghi, Mohammad Hossein; Brar, Satinder Kaur; Magdouli, Sara
Abstract: This work evaluated a green route for developing an eco-friendly flowsheet to regenerate base and precious metals from waste printed circuits boards (WPCBs). Copper (as nanoparticles with an average diameter of 50 nm) and other base metals were extracted via oxidative acid leaching with high efficiency. Thiocyanate was employed for the first time as a green and economical reagent for the extraction of gold from pretreated WPCB. The effect of various parameters, including reagent dosage and temperature, was evaluated on the gold leaching rate, and 100% gold dissolution was achieved at the optimal condition. It was found that ferric iron concentration as the gold leaching oxidant has a notable effect on gold extraction. Also, at temperatures above room temperature, the recovery rate increases in a short period and then decreases continuously. The activation energy of the optimum gold thiocyanate leaching was found to be 42.84 kJ/mol, indicating chemical reaction to be the rate-controlling step. Gold extraction from the thiocyanate medium was carried out by employing activated carbon, where 100% gold adsorption was achieved in 2 h. Toxicity assessment of final residue revealed that it could be categorized as an environmentally safe waste with negligible risk. Graphical abstract: Image 1 Research Highlights: Hazardous base metals were removed by pretreatment and oxidative leaching. Almost 100% of precious metals, including Au and Ag, were recovered. Kinetic modeling was performed on leaching rate. Cu nanoparticles and gold extracted from PLS of oxidative and thiocyanate leaching. Toxicity of solid residues and economical aspects of the process were studied.